2004
DOI: 10.1590/s0100-69912004000100002
|View full text |Cite
|
Sign up to set email alerts
|

Câncer do esôfago: complicações pós-operatórias imediatas e letalidade hospitalar

Abstract: Carlos Estevão Frimm, ECBC-SP 3João Fava, TCBC-SP 3 RESUMO: Objetivo: O objetivo deste estudo é verificar as variáveis que podem influenciar as complicações pós-operatórias imediatas e a mortalidade hospitalar dos pacientes portadores de câncer do esôfago submetidos a tratamento cirúrgico. Método: Por meio de análise retrospectiva de 60 pacientes verificamos, pela análise uni e multivariada, se variáveis como procedência, tempo de história, doenças prévias, tabagismo, etilismo, perda ponderal, localização do t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
14

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
(26 reference statements)
0
2
0
14
Order By: Relevance
“…Compared with results from the literature 4,7,8 , which show an incidence of fistulas up to 50%, cervical esophagogastric anastomosis with invagination had a low incidence of fistula formation, with only one case (1.8%) having important clinical repercussion.…”
Section: Discussionmentioning
confidence: 52%
“…Compared with results from the literature 4,7,8 , which show an incidence of fistulas up to 50%, cervical esophagogastric anastomosis with invagination had a low incidence of fistula formation, with only one case (1.8%) having important clinical repercussion.…”
Section: Discussionmentioning
confidence: 52%
“…There was a prevalence of Stage III and IV tumors of about 88%, with a higher percentage, around 95%, in the minor surgery group. Oka et al (20) showed the presence of advanced stage (II & IV) tumors in 60% of patients and Gagliardi et al (14) in 53.4%; these studies did not prioritize patients with removable tumors, as in this investigation. Therefore the percentage of advanced malignant esophagus disease in this study is much higher than in consulted literature and only lower than exclusively palliative studies where all patients had stage III & IV (11) .…”
Section: Discussionmentioning
confidence: 84%
“…Na literatura nacional, Gagliardi et al 6 , analisando as complicações pós-operatórias de doentes submetidos à operação paliativa e radical para câncer do esôfago, relatam que as complicações pleuro-pulmonares foram as mais frequentes, atingindo 43,3%. Tomasich et al 36 relatam também complicações pleuropulmonares elevadas nos doentes operados e submetidos ao tratamento neoadjuvante e mortalidade hospitalar de 13,7%.…”
Section: Discussionunclassified
“…Com relação às complicações pós-operatórias, independentemente do tipo de operação realizada, as de natureza respiratória e as deiscências de anastomose, associadas ou não à mediastinite e/ou sepse, são as mais referidas na literatura como causas dos óbitos 6 .…”
Section: Introductionunclassified